RARELY REPORTED SPECIES OF INDONESIAN SEA CUCUMBERS - Wirawati, Ismiliana; Purwati, Pradina (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2012)
More than 300 sea cucumber species have been recorded from Indonesian waters. This paper presents eight species which have been rarely reported. Actinopyga bannwarthi Panning, 1944, were found among fished sea cucumbers collected by fishermen in Kupang and Karimunjawa. Stichopus pseudohorrens Cherbonnier, 1967, was found in West Timor waters; Thelenota rubralienata Massin & Lane, 1991, and A. caerulea Samyn, Vandenspiegel & Massin, 2006, were collected from the reef in Halmahera, North Maluku. Four other species i.e. Bohadschia atra Massin, Rasolofonirina, Conand, Samyn, 1999; B. subrubra Quoy and Gaimard, 1833; Holothuria (Metriatyla) fuligina Cherbonnier, 1988, and H. (Thymiosycia) gracilis Semper, 1868, were discovered from Lombok waters. The latest mentioned species was also found among fished sea cucumbers in Karimunjawa. All species except T. rubralineata may be new records for Indonesia. In the case of H. (Thymiosycia) gracilis Semper, 1868, it was new record for Lombok waters, following its discovery from West Seram, Central Maluku.